KOMUNIKASI PEMASARAN RUMAH SAKIT ISLAM MALAHAYATI DALAM MENINGKATKAN KUNJUNGAN PASIEN DI KOTA MEDAN - Andina Herfiza; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Marketing is one of the main activities of the company to be able to maintain its survival, to grow and earn profit. Therefore, there needs to be coordination and cooperation from parties involved in marketing business. Marketing communication is a series of process activities conducted by individuals or a group or organization, namely planning thinking, pricing, promotion and distribution of ideas, goods, to meet the needs, desires and demands of consumers. This study aims to determine marketing communications conducted by Malahayati Islamic Hospital based on the implementation of marketing Based on the research that has been done, it is known that the implementation of marketing communications conducted by Malahayati Islamic Hospital includes advertising through the distribution of brochures only. This research was conducted at Malahayati Islamic Hospital of Medan. This research uses descriptive qualitative method, with purposive technique. In this study selected 2 respondents from marketing sub division, 1 respondent from sub division of public relations and 1 respondent from information section of Malahayati islamic hospital and 7 consumer chosen using accidental sampling technique. Data collection techniques used are observation, interview and documentation. The result of the research shows Islamic Malahayati Hospital in carrying out marketing communication activities including marketing communications implementation conducted by using mixed marketing communications, advertising, personal selling, sales promotion, direct marketing and public relations. After that with evaluation activities conducted every monthKey words : Marketing Communication, Malahayati Islamic Hospital, Consumen Behavior